2006
DOI: 10.1002/path.2091
|View full text |Cite
|
Sign up to set email alerts
|

A candidate precursor to serous carcinoma that originates in the distal fallopian tube

Abstract: The tubal fimbria is a common site of origin for early (tubal intraepithelial carcinoma or TIC) serous carcinomas in women with familial BRCA1 or 2 mutations (BRCA+). Somatic p53 tumour suppressor gene mutations in these tumours suggest a pathogenesis involving DNA damage, p53 mutation, and progressive loss of cell cycle control. We recently identified foci of strong p53 immunostaining-termed 'p53 signatures'-in benign tubal mucosa from BRCA+ women. To examine the relationship between p53 signatures and TIC, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

35
784
2
15

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 793 publications
(854 citation statements)
references
References 31 publications
35
784
2
15
Order By: Relevance
“…Beginning in 2000, a progressive accumulation of data has implicated the distal fallopian tube as a site of origin of HGSC by identification of precursors in tubal epithelium [2][3][4][5]. As a consequence, in addition to clinical management guidelines recommending salpingo-oophorectomy for women with germ-line mutations in BRCA1 or BRCA2, recommendations have been published for opportunistic salpingectomy as a cancer preventive in women who are not at increased risk for ovarian cancer [9][10][11].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Beginning in 2000, a progressive accumulation of data has implicated the distal fallopian tube as a site of origin of HGSC by identification of precursors in tubal epithelium [2][3][4][5]. As a consequence, in addition to clinical management guidelines recommending salpingo-oophorectomy for women with germ-line mutations in BRCA1 or BRCA2, recommendations have been published for opportunistic salpingectomy as a cancer preventive in women who are not at increased risk for ovarian cancer [9][10][11].…”
Section: Discussionmentioning
confidence: 99%
“…As a consequence, attention is now heavily focused on therapies and interventions aimed at prevention. Due to research on early serous carcinogenesis in the last 10-15 years, many cases of HGSC are now believed to arise from the distal fallopian tube in the form of serous tubal intraepithelial carcinoma (STIC) [2][3][4][5]. Thus, in addition to prophylactic salpingo-oophorectomy, which is a powerful risk-reducing intervention for women with germ line BRCA1 or BRCA2 mutations, [6,7] [8,9] the Society of Gynecologic Oncology (2013) and American College of Obstetricians and Gynecologists (2015) have suggested that opportunistic salpingectomy be considered at the time of hysterectomy for "averagerisk" (alternatively "low-risk") women after the completion of child bearing to reduce the risk of a later HGSC [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…8 These expansions, termed 'p53 signatures' are currently the most plausible precursor candidates to high-grade serous cancers developing in the oviduct. 8,10,16 However, it is known that in addition to loss of TP53 function, numerous other disturbances in gene expression characterize high-grade serous cancers, and it is logical to presume that precursors contain some of these functional alterations. 17,18 One of these genes, PAX2, has been shown to be down-regulated in both high-grade mü llerian (endometrioid or serous) pelvic carcinomas and in benign and neoplastic endometrium.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, loss of PAX2 staining was also highly prevalent in p53 signatures, secretory cell expansions with p53 mutations that are candidate precursors. 8 The presence of two forms of secretory cell expansion showing PAX2 dysregulation in the oviduct underscored the need to understand the distribution of this phenomenon and its relationship to age and neoplasia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation